KEANEKARAGAMAN JENIS BURUNG PADA AREAL DONGI-DONGI DI KAWASAN TAMAN NASIONAL LORE LINDU - Nugroho, Mikhael Satrio; Ningsih, Sri; Ihsan, Moh. (Warta Rimba, 2013)
This research was conducted on May 2013 - July 2013 in Dongi-Dongi area at Lore-Lindu National Park, to determine the species composition, attendance rates, species diversity, composition based on category guild and species evenness of birds. This rescarch used transect method. Data were collected using four units of 500 m line transect each. For residential area and around forest habitat, it was found there are 45 species of bird within 25 families where 22 of them are endemic. In residential area there were 8 species with attendance rate of 100 %, 2 species of 75 %, 5 species of 50 % and 16 species of 25 %. Meanwhile, the diversity index in residential area (H) was 3.19 , and 3.17 in forest habitat. In addition, evenness in residential area and forest habitat ispectively (E) are 0. 93 and 0.89. Based on the category guild, 7 compositions found in residential area and 9 in forest habitat. Keywords: Diversity, bird species, forest, Dongi-Dongi residential.